2017
DOI: 10.26500/jarssh-02-2017-0402
|View full text |Cite
|
Sign up to set email alerts
|

Learning system management based on teaching factory in Indonesia

Abstract: This research goal is to discribe, 1) Character setting of learning which is based on Teaching Factory in SMK Muhammadiyah 1 Klaten, 2) Feature of teacher learning activity which is based on Teaching Factory in SMK Muhammadiyah 1 Klaten, 3) Feature of students learning activity which is based on Teaching Factory in SMK Muhammadiyah 1 Klaten. This kind of research is qualitative and using ethnography design. This reseach was done in SMK Muhammadiyah 1 Klaten. The main subject in this research is school manager … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…The implementation of e-commerce begins with taking pictures or documentation on the product of the State Vocational High School 3 South Tangerang production unit. This step aims to ensure that the content generated on the e-commerce account is more attractive to consumers and neatly organized [20]. The documentation taken includes workshops and some sample products.…”
Section: Taking Photos or Product Documentationmentioning
confidence: 99%
“…The implementation of e-commerce begins with taking pictures or documentation on the product of the State Vocational High School 3 South Tangerang production unit. This step aims to ensure that the content generated on the e-commerce account is more attractive to consumers and neatly organized [20]. The documentation taken includes workshops and some sample products.…”
Section: Taking Photos or Product Documentationmentioning
confidence: 99%
“…Its main characteristic is that the school lays a basic vision that students are intact personalities (Wahjusaputri, Fitriani, Indah Nastiti, & Syukron, 2020). Furthermore (Haris, 2017) found that in the learning process, the students are ready to have the skill and good character, as well as give them some competencies so they will be ready to work or become a businessman after graduation. The teaching factory consisted of planning, organizing, implementing, and evaluating.…”
Section: Culinary Competence Program Evaluation and Follow-up At Voca...mentioning
confidence: 99%
“…Therefore, this fact requires State Vocational High School 4 Mataram to be able to align and balance the units in the micro-education system concerning inputs, processes, and outputs, as described by Haris (2017) "The headmaster, should pay more attention to balance the input, process, and output in the process of teaching factory based...". This means that schools should balance inputs, processes, and graduates into teaching factory-based learning.…”
Section: Supporting Factors Of Teaching Factory Learning At State Vocational High School 4 Matarammentioning
confidence: 99%